Analisis Hubungan Kausalitas Antara Jumlah Uang Beredar Dengan Inflasi Di Indonesia (1981 - 2015) - Susilowati, Indah; , Dr. Daryono Soebagyo, MEc (2016)
This study entitled "Causality Relationship between Money Supply Inflation in Indonesia (1981-2015)". The purpose of this study was to determine the pattern or direction of causality between money supply and inflation in Indonesia in the short term and long term based on the time period from the year 1981-2015. Data used in this research is secondary data, money supply and inflation in Indonesia, the analysis method used is the Sims causality test is to determine whether the inflation affect or cause the money supply, and the money supply affect or cause inflation. The results of this study can be concluded that the variables of money supply stationary positive effect on inflation while the inflation variable stationary positive effect on the money supply in Indonesia.